A névelemek sorrendje és kulturális kongruenciája a Borsszem Jankó zsidó figuráinak névanyagában a 20. század első felében - Luca Anna Németh (Névtani Értesítő, 2013)
Order and cultural congruence of the elements in personal names for Jewish characters appearing in a Hungarian humour magazine entitled Borsszem Jankó in the first half of the 20th century